PERBAIKAN TATA LETAK FASILITAS UNTUK EFISIENSI PEMINDAHAN BAHAN DI PT. ADI SATRIA ABADI YOGYAKARTA - Nisya Fitri Febriani; Rofiatun Nafiah (Politeknik ATK Yogyakarta, 2018)
One of the things that affects production process is the layout of the facility. This research aims to observe the influence of facility layout on material transfer efficiency. Efficiency is associated to time saving, effort and cost. Observations were conducted in PT. Adi Satria Abadi, Sleman, Yogyakarta. The material studied is the measurement of facility layout for material transfer efficiency. This research uses observation and documention methods to gain the data; meanwhile experiment and time counting on material transfer were done to solve the problem in order to improve layout efficiency. The layout of production facilities, which is based on the process at PT. Adi Satria Abadi, raises a waste of time and needs to increase efficiency in the material transfer process. Proposed improvements to the layout of facilities are carried out by changing the layout of facilities according to the order of the production process (layout based on products) to expedite the production process. The layout of facilities based on products is more efficient for PT. Adi Satria Abadi with the calculation of efficiency after improvement reached 93%.